Security Standard Recommendation of Teleworking in Government - Susilo Gumilang; Rudy Sutanto; Ahmad G. Dohamid (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Information technology and the internet are important factors in human life especially in works. Almost 70% of human works uses information technolgy, but since the restrictions on activities due to COVID-19 pandemic  have caused people to be able to do work in office as before. Some companies and government sectors that still have to carry out their business  processes require their employees to work remotely (teleworking) from home by utilizing the internet network. However, teleworking can pose a risk to the security of work data and personel data so there needs to be carrid out with minimal risk. This study uses a qualitative method with a literature approach to analyze the risks that arise from teleworking, classification of data that should not be disseminated, analyze the internet network, data protection and apply the theory of cyber security, network security, authentication and non-repudiation. Then apply these theories in a framework to develop security standards in teleworking. The final result of this research is a recommendation of regulatory standards for every government in conductiong teleworking.